THE EVALUATION OF CHEMICAL AND SENSORY PROPERTIES OF SOYBEAN-CORN TEMPEH FERMENTED WITH VARIOUS RAPRIMA YEAST CONCENTRATION AND VARIOUS FORMULATION - yana, Eli (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2017)
The purposes of research were to obtain the changes of chemical and sensory properties due to differences in yeast concentration and defferent of formulatation, the best of yeast concentration and formulation soybean-corn that produced the soybean-corn tempeh with the best chemical and sensory properties. The factorial experiment was arranged in a Complete Randomized Block Design (CRBD) with two factors and 3 replications. The first factor was formulation of soybean:corn P1 (90%:10%); P2 (80%:20%); P3(70%:30%); and P4 (60%:40%) w/w and the second factor was the yeast concentration with three levels; 0,5%; 1% ; and 1,5% w/w. The data were analyzed using ANOVA and further tested using Orthogonal Polynomials at levels of 5%. The results showed that the higher concentration of yeast on the soybean-corn tempeh increased the level of pH, ash content, protein content, and crude fiber soybean-corn tempeh. The higher concentration of corn added in the formulation has caused the increased of the moisture and flavor but decrease in the fat soybean-corn tempeh. The best treatment was found in yeast concentration 1,5% and formulation of soybean-corn 60%:40%. The tempeh recieved sensory test score of 3,37 compactness (rather compact), 3,13 for color (rather yellowish white), 3,82 for aroma (typical tempeh soybean-corn), and for acceptance of the overall 3,32 (rather like), pH was 4,62-5,10, moisture of 70,54%, ash content of 1,36%, the fat content of 11,11%, protein of 12,72 and crude fiber of 8,46%. Key words: Raprima, soybean-corn tempeh, yeast